Influence of Video Health Education on Knowledge and Attitudes toward Menopausal Nutrition. - Putri, Sabilla; Pipitcahyani, Tatarini Ika; Sukesi, Sukesi; Rijanto, Rijanto (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
Menopause is a condition with a decrease in reproductive physiological function in women which results in a decrease in ovarian function which can result in a reduction and possibly a loss of reproductive estrogen. This research is a type of quantitative research with a research design using Quasy experiment with a pre-test post-test control group approach of 32 respondents divided into treatment groups and control groups. By using the research design "Non Equivalent Control Design" or "Non Randomized Control Group Pretest-Postest Design", namely research to compare the results of interventions in the experimental group and the control group by sampling without purposive sampling. Statistical test results using the Wilcoxon Signed Rank Test in the treatment group, a significant value (p) of 0.001 was obtained, which was smaller than α 0.05, so the hypothesis was accepted, and in the control group, after the Wilcoxon test was carried out, a significant value (p) of 0.011 was obtained, which was greater than α 0.05, so the hypothesis was rejected, and it could be It can be seen that in the treatment group there are significant attitude values, while in the control group there are no significant differences in attitude values. The results of statistical tests using the Mann Whitney U Test obtained a significant value (p) of 0.000, which is smaller than α 0.05 so that the hypothesis was accepted.